Direct-acting antivirals in relapsed or refractory hepatitis C virus-associated diffuse large B-cell lymphoma. Issue 9 (28th July 2020) - Merli, Michele; Defrancesco, Irene; Visco, Carlo; Besson, Caroline; Di Rocco, Alice; Arcari, Annalisa; Sica, Antonello; Cencini, Emanuele; Tisi, Maria Chiara; Frigeni, Marco; Grossi, Paolo; Bianchi, Benedetta; et al.
Abstract: Recent studies have demonstrated feasibility and substantial benefit of direct-acting antivirals (DAAs) administration during or after first-line immune-chemotherapy (I-CT) in patients with hepatitis C virus (HCV)-positive diffuse large B-cell lymphomas (DLBCL). However, data on DAAs used during or after salvage treatments are still lacking. In this study we assessed clinical and virological outcome in 11 patients with relapsed ( n = 7) or refractory ( n = 4) HCV-positive DLBCL. DAAs were given either concurrently ( n = 3) or subsequent ( n = 8) to salvage I-CT. Most patients (10 of 11) received sofosbuvir-based regimens. All patients completed their planned courses of DAAs and achieved sustained virological response. DAAs were well tolerated, with no grade ≥2 adverse events. At a median follow-up of 3.6 years four patients died (4-year OS: 76%). In conclusion, we provide evidence that DAAs in HCV-positive relapsed/refractory DLBCL are extremely safe and effective, suggesting that they should be used if HCV eradication was not instituted before.